FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENGGUNAAN APD DIANTARA TENAGA KESEHATAN ZONA MERAH COVID 19 DI RUMAH SAKIT “X” TAHUN 2022 - ALATAS SOFAN SUGARA; BYBA MELDA (NHM PRESS, 2022)
PPE plays an important role in preventing the transmission of the Covid-19 virus among health workers. The purpose of the study was to determine the factors related to the behavior of using PPE among health workers in the Covid 19 red zone at the